Expectations of a Post-Wwii Depression - Thies, Clifford F. (Studia Historiae Oeconomicae, 2021)
The forecast of a Post-WWII depression is contrasted against the vigorous growth that actually happened. Economists called for continued control over the economy to prevent the feared depression. But, in spite of the warning, returning soldiers were rapidly demobilized and the economy decontrolled. While economists dismissed indications toward the end of the war of pent-up demand as unsustainable, pent-up demand played an important role in the smooth transition from a wartime to a peacetime economy. Indicators of pent-up demand included buying plans and the accumulation of liquid assets. This study tracks expectations of a post-war depression of the general public, business and economists during this period. It shows that, in 1947, all three groups expected a recession, if not a depression. Yet, no such thing occurred. In the case of the general public, a time series of expectations is extracted from heterogeneous survey data.